Keterkaitan Pertumbuhan Ekonomi Daerah dengan Aspek Infrastruktur Non Fisik - Daeli, Sorni (Jurnal Bina Praja, 2009)
This study aims to provide an overview of the relationship between non-physical infrastructure and regional economic growth. For this purpose, secondary data from BPS in 2007 is required. The analysis uses quantitative secondary data analysis techniques using regression models in the form of cross-sections. The results show the relationship of non-physical infrastructure aspects to regional economic growth, such as: income per capita per year, literacy rate and population density. This study suggests that the government should improve its ability to provide the non-physical infrastructure needed by the community, especially those needed for SOM empowerment. It is also suggested that the government should gradually move the concentration of industries to areas outside Java by providing adequate infrastructure facilities and infrastructure, so that the population is not only focused on the island of Java but is spread evenly across other islands in Indonesia.